2019
DOI: 10.1111/ggi.13693
|View full text |Cite
|
Sign up to set email alerts
|

Does transpersonal trust moderate the association between chronic conditions and general practitioner visits in the oldest old? Results of the AgeCoDe and AgeQualiDe study

Abstract: Aim The purpose of this study was to investigate whether transpersonal trust (TPT) moderates the relationship between chronic conditions and general practitioner (GP) visits among the oldest old in Germany. Methods The multicenter prospective cohort Study on Needs, health service use, costs and health‐related quality of life in a large sample of oldest old primary care patients (85+) (AgeQualiDe) was carried out. Individuals were recruited through GP offices at six study centers in Germany (follow‐up wave 7). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…At first glance, it may seem contradictory that both higher loneliness and greater life satisfaction are associated with a greater likelihood of using online consultations. However, previous research has also demonstrated a link between increased loneliness and an increased number of GP visits [34]-for example, to address social needs in higher age [35]. Furthermore, the association between life satisfaction and online consultations may be explained by the fact that life satisfaction is positively associated with an increased use of preventive health care services (eg, in women: higher likelihood of obtaining a mammogram, x-ray, or pap smear; in men: higher likelihood of obtaining a prostate examination) [36].…”
Section: Previous Research and Possible Explanationsmentioning
confidence: 99%
“…1 We argue that a more holistic approach for the care of elderly, chronically ill patients is needed which considers three aspects strongly linked to self-efficacy: patients' spiritual needs, social activity and self-care, i.e., patients' activeness in areas that can enhance well-being other than taking medication. [2][3][4] Studies show that patients have voiced the wish for holistic attention from their physician, 5,6 while many GPs acknowledge that meeting these needs should be an integral part of primary care. 4,[7][8][9] At the same time, patients and GPs alike report a lack in competencies on the part of the physician in terms of providing holistic primary care, in particular in meeting patients' spiritual needs.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Studies show that patients have voiced the wish for holistic attention from their physician, 5,6 while many GPs acknowledge that meeting these needs should be an integral part of primary care. 4,[7][8][9] At the same time, patients and GPs alike report a lack in competencies on the part of the physician in terms of providing holistic primary care, in particular in meeting patients' spiritual needs. 10 Insufficient training offered in the medical school curriculum, as well as in continuous medical education seems to be a major part of the problem.…”
Section: Introductionmentioning
confidence: 99%